92 'Will it hurt?': Addressing hospital related anxiety in children and identifying their information needs. (23rd February 2023) - Sharma, Ambika; Bowyer, Stuart A; Pissaridou, Eleni; Sebire, Neil J; Visram, Sheena; Rogers, Yvonne
Abstract : It can be overwhelming and frightening to deal with health issues for children and young people. They are often intimidated by hospitals and information given by clinicians that is beyond their comprehension. The fear of unknowing often associates hospitals with anxiety and uncertainty in children and young people. The purpose of this study is to identify needs, so that it is possible to address concerns and reduce anxiety in children and young people to make their healthcare journey well informed. We conducted scenario-based interviews and co-design sessions with a group of children (n=9) aged between 12-17 who were members of GOSH Young Persons' Advisory Group (YPAG). The sessions focused on gathering thoughts and emotions they feel when visiting a hospital and identifying their information needs. Our findings revealed that the entire group associated negative emotions when given a scenario about diagnosis and treatment of a long-term health condition. Many participants admitted they'll feel 'nervous, stressed, confused and discouraged' before going for a treatment or procedure, while some expressed concerns about its effect on their mental and physical health and how painful it would be. They also probed about the short term and long-term prognosis of the condition, if they can refuse treatment and how long will they have to miss school. When asked about what will help them prepare better for their hospital visits, 86% of the participants voted for data visualizations of their condition and risk levels and 71% expressed interest in knowing details about the procedure and an ideal recovery timeline. 57% of the participants agreed that knowing the environment of the hospital and the people they'll be meeting beforehand will help in reducing anxiety. These findings support the use of digital information systems for children undergoing medical treatment to reduce pre-operative anxiety and negative emotions.